2004
DOI: 10.1002/cncr.20028
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic hypogonadism in male survivors of cancer with chronic exposure to opioids

Abstract: BACKGROUND Profound hypogonadism has been noted in patients receiving intrathecal opioids. The purpose of the current study was to determine whether chronic consumption of oral opioids by male survivors of cancer also would lead to central hypogonadism and whether this hypogonadism was associated with symptoms of sexual dysfunction, fatigue, anxiety, and depression. METHODS A case–control study was conducted at The University of Texas M. D. Anderson Cancer Center (Houston, TX), in which 20 patients who were ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
109
1
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 191 publications
(117 citation statements)
references
References 51 publications
3
109
1
4
Order By: Relevance
“…The trend toward higher opioid dosage for hypogonadal patients is consistent with previous reports, 45 including our own, 44,49 of hypogonadism among cancer survivors without evidence of recurrent disease who use opioid therapy for chronic pain. Our patients with autonomic dysfunction did not seem to have a greater frequency of fatigue or, indeed, of any major symptoms except for dyspnea.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The trend toward higher opioid dosage for hypogonadal patients is consistent with previous reports, 45 including our own, 44,49 of hypogonadism among cancer survivors without evidence of recurrent disease who use opioid therapy for chronic pain. Our patients with autonomic dysfunction did not seem to have a greater frequency of fatigue or, indeed, of any major symptoms except for dyspnea.…”
Section: Discussionsupporting
confidence: 91%
“…This confirms our previous observation in patients with cancer who received opioids. 44 Elevated inflammatory cytokines, particularly IL-6, are common in patients with advanced cancer and are associated with fatigue, depression, anorexia/ cachexia, reduced free testosterone, prolonged suppres-FIGURE 1. Free testosterone versus total testosterone (in ng/mL) (normal free testosterone is !34 ng/mL; normal total testosterone is !241 ng/mL).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in a placebo-controlled trial among overweight, otherwise healthy men, vitamin D replacement over a period of 1 year significantly increased testosterone levels [23]. In patients with cancer, chronic use of opioid analgesics can result in low testosterone [24], and in combination with low vitamin D levels this could predispose patients to loss of muscle mass and increase the insulin resistance associated with cancer cachexia [25] or obesity. Both vitamin D [26] and testosterone [27] supplementation have been reported to increase insulin sensitivity in selected noncancer populations.…”
Section: Discussionmentioning
confidence: 99%
“…49 -52 Rajagopal et al 53 reported low TT levels in 18 of 20 cancer survivors who were receiving high-dose opioids orally (Ն200 mg of morphine equivalent daily dose for Ն1 year) compared with 8 of 20 matched cancer survivors who had not received opioids, suggesting that hypogonadism is common in cancer survivors and is even more common in patients who require high doses of opioids. Nevertheless, samples were not drawn in the early morning, and neither SHBG nor FT levels were measured.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, all blood specimens were obtained in the early morning, in contrast to most of the previous studies, 45,53 in which samples were collected throughout the day. This is particularly important, because testosterone is characterized by a diurnal rhythm, with highest levels in the morning and a nadir in the late afternoon.…”
Section: Discussionmentioning
confidence: 99%